From Behaviorism to Cognitive Neuroscience: An 83-Year Bibliometric Analysis of Mental Arithmetic Research in Educational Psychology (1942–2024) - Leiden Levita Sahensolar; Isma Widiaty; Mubiar Agustin (FKIP Universitas Lampung, 2026)
This study addressed the absence of a comprehensive bibliometric analysis of mental arithmetic research in educational psychology by systematically mapping its evolutionary trajectory over 83 years (1942–2024). Using Scopus database searches, 1,749 unique deduplicated records were retrieved, with 626